2015
DOI: 10.1513/annalsats.201312-430oc
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal and Hilar Lymph Node Measurements. Comparison of Multidetector-Row Computed Tomography and Endobronchial Ultrasound

Abstract: Our single-center study shows that there was poor correlation between computed tomography and endobronchial ultrasound for the measurement of mediastinal and hilar lymph nodes. Malignant cells were recovered by ultrasound-guided needle aspiration from a substantial fraction of lymph nodes that were initially interpreted as normal in size. If these findings are confirmed, new criteria may be needed for lymph node measurement on computed tomography that will guide selection of lymph nodes for endobronchial ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Also, when assessing the upper limits of the reference interval, the coronal axes diameters often exceeded the generally used cut-off points of 10 mm for the short axis and 15 mm for the long axis. This is comparable to earlier research on the coronal short and long axis of hilar and mediastinal lymph nodes [14,15]. Therefore, the coronal axes of abdominal lymph nodes in children should not be used to interpret whether a lymph node is enlarged based on criteria for axial measurements.…”
Section: Discussionsupporting
confidence: 83%
“…Also, when assessing the upper limits of the reference interval, the coronal axes diameters often exceeded the generally used cut-off points of 10 mm for the short axis and 15 mm for the long axis. This is comparable to earlier research on the coronal short and long axis of hilar and mediastinal lymph nodes [14,15]. Therefore, the coronal axes of abdominal lymph nodes in children should not be used to interpret whether a lymph node is enlarged based on criteria for axial measurements.…”
Section: Discussionsupporting
confidence: 83%
“…Increased MLN size has been strongly linked to more advanced stages of malignancy and greater mortality (43,44). Fourth, there is abundant evidence in health and disease that noninvasive CT assessment of MLN enlargement correlates fairly well with more invasive techniques such as endobronchial ultrasound measurements (21,45). Thus, preliminary CT evaluation is almost always used to guide MLN sampling and tissue procurement for diagnosis and planning therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The performing radiologist provided MLN measurements from the reformatted imaging data using virtual calipers. MLNs with a short-axis diameter >10 mm were reported as enlarged (21)(22)(23). MLN stations based on the International Association for the Study of Lung Cancer nomenclature were systematically assessed for enlarged lymph nodes (22).…”
Section: At a Glance Commentarymentioning
confidence: 99%
“…Udoji and colleagues [14] also recently demonstrated a poor correlation between CT and EBUS for the measurement of mediastinal and hilar lymph nodes. They reported a correlation coefficient of 0.44, very similar to that of the present study (r ¼ 0.49), suggesting a statistically moderate correlation between the two modalities.…”
Section: Commentmentioning
confidence: 99%
“…A recent study has demonstrated a poor correlation between CT and EBUS for the measurement of mediastinal and hilar nodes, thus questioning the use of lymph node sizes measured on CT scan to decide on the need for EBUS [14]. Although the measurement of another mediastinal structure, namely the pulmonary artery size on EBUS, statistically correlates with that on CT scan, the limits of agreement are too wide for a clinically meaningful correlation [15].…”
mentioning
confidence: 99%